Analisis Penyusunan Laporan Keuangan Koperasi Simpan Pinjam “Mandiri Sejahtera” Berdasarkan SAK ETAP Financial Statement Analysis of “Mandiri Sejahtera” Cooperative Under SAK ETAP - Adrian Fharas Yuandra Putra; Azahra Nur Fadhilah; Dela Sukma Pangestu; Maureen Imbruglia Marcus; Nabila Nur Andini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Cooperatives play a significant role in Indonesia’s economic system because they aim to enhance member welfare through collective ownership and cooperative principles. To maintain accountability, cooperatives are required to prepare financial reports following the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). This study examines how SAK ETAP is applied in the financial reporting practices of Koperasi Simpan Pinjam (KSP) Mandiri Sejahtera, Comal Branch. Using a qualitative descriptive method with a case study approach, data were gathered through interviews and an analysis of the 2022 financial statements. The results indicate that although the cooperative has implemented several elements of SAK ETAP, full compliance has not been achieved due to limited human resources and the absence of an integrated reporting system. Nevertheless, the preparation of PPAP reports reflects prudence in managing credit risk and highlights the need for digital systems and improved accounting skills to strengthen transparent and accountable financial management.